Information analysis of online collaborative company review - Timothy Rey Laheba; The Jin Ai (Journal of Management and Business, 2021)
In this era of industry 4.0, the role of technology is getting bigger and broader in the industry. This technology has changed some of the old habits and paradigms in the relationship between companies and job seekers. One of the changes currently occurring is that job seekers can find information related to a company through an online collaborative company review which can be found easily on the employment website. This study aims to determine what information job seekers consider essential from an online collaborative review of a company. Data from the 203 millennial generations in Indonesia were collected. The study results found that the most sought-after variable from an online collaborative company review was Basic salary exposition, followed by Job description. The following variable is Work-life balance or working condition, followed by the Company profile variable, Benefits and incentives, Positive things about a company, and negative things about a company.